2015
DOI: 10.1515/sdj-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

XP-endo Finisher: A New Solution for Smear Layer Removal

Abstract: Introduction The aim of this study was to evaluate using SEM analysis the effectiveness of a new instrument XP-endo Finisher in cleaning root canal walls after instrumentation with BioRaCe NiTi rotary instruments. Material and Methods This in vitro study was conducted on 30 extracted single rooted teeth divided in two groups. Instrumentation of all canals was done using basic BioRaCe NiTi rotary instruments with copious irrigation of 2% NaOCl. In the first group, after complete instrumentation smear layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 23 publications
4
16
1
1
Order By: Relevance
“…Earlier investigations used light microscopy to identify the smear layer on the canal walls, but today SEM analysis is the standard in the field of quantitative and qualitative estimation of the presence of the smear layer due to high resolution and high magnification [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier investigations used light microscopy to identify the smear layer on the canal walls, but today SEM analysis is the standard in the field of quantitative and qualitative estimation of the presence of the smear layer due to high resolution and high magnification [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that XP-endo Finisher, which is used for the final debridement of the root canal, due to its specific design and extreme flexibility (it changes shape during instrumentation), can reach the inaccessible parts of the canal system [7,20,24].…”
Section: Discussionmentioning
confidence: 99%
“…Clean canal walls in apical third of the nearly all samples could be explained primarily by the simplicity of canal morphology, but also by the effects of the new XPS instrument, or by its specific design, at a speed of 800 rpm, and by the fact that it can change its shape in the canal during the instrumentation and thus, reach the inaccessible canal areas 17,25 . In addition, the extreme flexibility of the XPS and the working end with 6 cutting edges (with minimal torque) ensure efficient cleaning of all canal walls and the apical segment.…”
Section: Discussionmentioning
confidence: 99%
“…Exceptional and prolonged antibacterial effect of chlorhexidine on the large number of bacteria in the canal, makes this irrigant often used in endodontic treatments 8,14 . Researches has also shown that it is possible to increase the efficiency of the irrigant, or to achieve better penetration and better cleaning of the canal walls using some forms of solution activation like: ultrasound 15,16 , a new instrument XP-endo Finisher 1,17 or laser 18 .…”
Section: Sem Analysismentioning
confidence: 99%
“…Evaluation of the power of XP-endo Finisher files after chemomechanical preparation in cleaning the coronal, middle and apical third. These resulted that using XP-endo Finisher after chemomechanical preparation effectively cleaned canal walls and removed smear layer (18,19) . Other studies compared the effect of XP-endo Finisher files and other agitation techniques.…”
Section: Introductionmentioning
confidence: 96%